The antecedent effect of the service quality dimension on customer satisfaction on word of mouth (Study on Perumdam Maruang Duhung) - Bryanviko, Mayrichael; Meitiana, Meitiana; Kristinae, Vivy; Karuehni, Ina (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
This study aims to analyze how much the antecedent of the service quality dimension on customer satisfaction affects word of mouth. This research was conducted on Perumdam customers domiciled in Kuala Kurun, with a sample of 80 respondents determined through predetermined criteria. Data collection was carried out by sharing questionnaires through Google forms. This study uses the analysis of the Partial Least Squares (PLS) model to evaluate the relationship between variables. The results show that the variables of assurance, reliability, and empathy have a significant effect on customer satisfaction. Meanwhile, the variables of tangibles and responsiveness did not have a significant effect on satisfaction. For the customer satisfaction variable, it has a significant influence on word of mouth. This study highlights the important role of the service quality dimension on customer satisfaction so that it has an impact on providing positive comments.